“(…) é um rapaz cheio de sorte, digo-lhe já (risos)”: o humor como estratégia discursiva de mitigação do conflito (potencial) em interacções verbais na rádio” - Almeida, Carla Aurélia de (2017)
Taking as reference an oral corpus consisting of verbal interactions presented in Portuguese radio phone-in programmes, we proceed to the identification of the sequential dimensions of illocutionary acts and we study the selection, made by the participants, of the discourse strategies of humour which have laughs as a conversational resource for mitigation of potential conflict in interaction. We will analyze participant’s production of figures of enunciative distance like irony and humour in specific interaction sequences and we will verify the way these conversational devices contribute to the maintenance of the interactional order.